Differential YAP nuclear signaling in healthy and dystrophic skeletal muscle - Iyer, Shama R. (Am J Physiol Cell Physiol, 2019)
Mechanical forces regulate muscle development, hypertrophy, and homeostasis. Force-transmitting structures allow mechanotransduction at the sarcolemma, cytoskeleton, and nuclear envelope. There is growing evidence that Yes-associated protein (YAP) serves as a nuclear relay of mechanical signals and can induce a range of downstream signaling cascades. Dystrophin is a sarcolemma-associated protein, and its absence underlies the pathology in Duchenne muscular dystrophy. We tested the hypothesis that the absence of dystrophin in muscle would result in reduced YAP signaling in response to loading. Following in vivo contractile loading in muscles of healthy (wild-type; WT) mice and mice lacking dystrophin (mdx), we performed Western blots of whole and fractionated muscle homogenates to examine the ratio of phospho (cytoplasmic) YAP to total YAP and nuclear YAP, respectively. We show that in vivo contractile loading induced a robust increase in YAP expression and its nuclear localization in WT muscles. Surprisingly, in mdx muscles, active YAP expression was constitutively elevated and unresponsive to load. Results from qRT-PCR analysis support the hyperactivation of YAP in vivo in mdx muscles, as evidenced by increased gene expression of YAP downstream targets. In vitro assays of isolated myofibers plated on substrates with high stiffness showed YAP nuclear labeling for both genotypes, indicating functional YAP signaling in mdx muscles. We conclude that while YAP signaling can occur in the absence of dystrophin, dystrophic muscles have altered mechanotransduction, whereby constitutively active YAP results in a failure to respond to load, which could be attributed to the increased state of “pre-stress” with increased cytoskeletal and extracellular matrix stiffness.